2001
DOI: 10.1038/35070009
|View full text |Cite
|
Sign up to set email alerts
|

Membrane blebbing during apoptosis results from caspase-mediated activation of ROCK I

Abstract: The execution phase of apoptosis is characterized by marked changes in cell morphology that include contraction and membrane blebbing. The actin-myosin system has been proposed to be the source of contractile force that drives bleb formation, although the biochemical pathway that promotes actin-myosin contractility during apoptosis has not been identified. Here we show that the Rho effector protein ROCK I, which contributes to phosphorylation of myosin light-chains, myosin ATPase activity and coupling of actin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

48
1,028
5
13

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 1,138 publications
(1,094 citation statements)
references
References 30 publications
48
1,028
5
13
Order By: Relevance
“…Thus, U2OS cells were treated with 1530 distinct chemicals from the ICCB Known Bioactives Library or the US-Drug Collection (encompassing most US Food and Drug Administration-approved and some experimental drugs), alone or in combination with MTX, for 18 h, stained with quinacrine and then analyzed by automated, quantitative epifluorescence microscopy ( Figure 2a). This screen led to the identification of several compounds that are capable of preventing the MTX-triggered loss of quinacrine-dependent fluorescence (Figure 2b): monensin, which blocks intracellular trafficking and exocytosis; 38 blebbistatin, which inhibits myosin II, thereby blocking the apoptosis-associated blebbing of the plasma membrane; 39 Y-27632, which inhibits ROCK1, 40 a protein that -upon cleavage by caspase-3 -participates in apoptotic blebbing; 41,42 and mefloquine, which inhibits PANX1 channels. 43 Subsequent validation experiments confirmed that monensin, blebbistatin and several chemically-unrelated inhibitors of ROCK1 (i.e., Y-27632, bearing with a central aminoethyl group, and H-1152, characterized by a central sulfonyl junction) and PANX1 (i.e., the synthetic quinine analogue mefloquine and the disulfonic stilbene derivatives 4,4 0 -diisothiocyano-2,2 0 -stilbenedisulfonic acid (DIDS) and 4-acetamido-4-isothiocyano-stilbene-2,2-disulfonic acid (SITS)) blunt the loss of quinacrine fluorescence as triggered in U2OS cells by MTX (Figure 2c).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, U2OS cells were treated with 1530 distinct chemicals from the ICCB Known Bioactives Library or the US-Drug Collection (encompassing most US Food and Drug Administration-approved and some experimental drugs), alone or in combination with MTX, for 18 h, stained with quinacrine and then analyzed by automated, quantitative epifluorescence microscopy ( Figure 2a). This screen led to the identification of several compounds that are capable of preventing the MTX-triggered loss of quinacrine-dependent fluorescence (Figure 2b): monensin, which blocks intracellular trafficking and exocytosis; 38 blebbistatin, which inhibits myosin II, thereby blocking the apoptosis-associated blebbing of the plasma membrane; 39 Y-27632, which inhibits ROCK1, 40 a protein that -upon cleavage by caspase-3 -participates in apoptotic blebbing; 41,42 and mefloquine, which inhibits PANX1 channels. 43 Subsequent validation experiments confirmed that monensin, blebbistatin and several chemically-unrelated inhibitors of ROCK1 (i.e., Y-27632, bearing with a central aminoethyl group, and H-1152, characterized by a central sulfonyl junction) and PANX1 (i.e., the synthetic quinine analogue mefloquine and the disulfonic stilbene derivatives 4,4 0 -diisothiocyano-2,2 0 -stilbenedisulfonic acid (DIDS) and 4-acetamido-4-isothiocyano-stilbene-2,2-disulfonic acid (SITS)) blunt the loss of quinacrine fluorescence as triggered in U2OS cells by MTX (Figure 2c).…”
Section: Resultsmentioning
confidence: 99%
“…However, recent evidence suggests that ROCKs exert effects by means of Rho-independent pathways (Coleman et al, 2001;Sebbagh et al, 2001). Overexpression of dominant negative and constitutively active forms of RhoA during heart development causes cardiac dysfunction, resulting in dilation of the ventricles and atria (Sah et al, 1999).…”
Section: Figmentioning
confidence: 99%
“…The small GTPase Rho and its target Rho-associated protein kinases (Rho kinase, p160ROCK) [9,18,19] control cell adhesion [10] and motility [35] through reorganization of the actin cytoskeleton and regulation of actomyosin contractility [3] in a number of cellular processes, including vascular contraction [31], tumor invasion [12], penile erection [2], and apoptosis [4]. Further, several lines of evidence indicated that Rho-ROCK signaling also has been involved in cellular transformation.…”
Section: Introductionmentioning
confidence: 99%